Music and protest in 1968 - Kutschke, Beate; Norton, Barley, 1971- (Cambridge : Cambridge University Press, 2015)
"Music was integral to the profound cultural, social and political changes that swept the globe in 1968. This collection of essays offers new perspectives on the role that music played in the events of that year, which included protests against the ongoing Vietnam War, the May riots in France and the assassination of Martin Luther King, Jr. From underground folk music in Japan to anti-authoritarian music in Scandinavia and Germany, Music and Protest in 1968 explores music's key role as a means of socio-political dissent not just in the US and the UK but in Asia, North and South America, Europe and Africa. Contributors extend the understanding of musical protest far beyond the narrow view of 'protest song' to explore how politics and social protest played out in many genres, including experimental and avant-garde music, free jazz, rock, popular song and film and theatre music." from back cover.
Expressive revolutions: '1968' and music in the Netherlands -- Music as plea for political action: the presence of musicians in Italian protest movements around 1968 -- "This Is My Country": American popular music and political engagement in '1968' -- Spontaneity and Black Consciousness: South Africans imagining musical and political freedom in 1960s Europe -- Music and protest in Japan: the rise of underground folk song in '1968' -- Vietnamese popular song in '1968': war, protest and sentimentalism -- "There is No Revolution Without Song": 'new song' in Latin America -- "The Power of Music": anti-authoritarian music movements in Scandinavia in '1968' -- British rock: the short '1938', and the long -- '1968' and the experimental revolution in Britain -- Anti-authoritarian revolt by musical means on bothe sides of the Berlin Wall -- '1968' - the emergence of a protest culture in the popular music of the Eastern Bloc? -- Gendering '1968': womanhood in model works of the People's Republic of China and movie musicals of Hong Kong -- A revolution in sheep's wool stockings: early music and '1968' -- Music and May 1968 in France: practices, roles, representations
Originally published: 2013.
Includes bibliographical references and index.
Keywords: Popular music -- Social aspects -- History -- 20th century; Popular music -- Political aspects -- History -- 20th century; Popular music -- 1961-1970 -- History and criticism; Protest songs -- 20th century -- History and criticism; Nineteen sixty-eight, A.D.